1998
DOI: 10.1159/000023284
|View full text |Cite
|
Sign up to set email alerts
|

Androgens and Fetal Growth

Abstract: Boys are heavier than girls at term birth. Children with a 46,XY karyotype and androgen insensitivity syndrome (clinically complete form and/or proven mutations in the androgen receptor gene) were found to have a birth weight comparable to that of girls. These findings support the hypothesis that the difference in birth weight between boys and girls is generated by androgen action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 2 publications
4
44
0
1
Order By: Relevance
“…The magnitude of the increase we found in the 2nd birthweight in the fresh/frozen pairs of siblings of +222 g is in accord with prior studies (+244 g 4 in an Australian population, +250 g 10 and +286 g 6 in Danish populations), and far exceeds the +81 g attributable only to an increase in parity. These analyses also confirm results from prior studies of the increasing risk of LGA with higher maternal parity and BMI [13,25,26]; the increased risk of SGA with early fetal losses [27]; and the lower birthweight, longer gestation, and lower risk of LGA in female versus male infants [28][29][30].…”
Section: Discussionsupporting
confidence: 85%
“…The magnitude of the increase we found in the 2nd birthweight in the fresh/frozen pairs of siblings of +222 g is in accord with prior studies (+244 g 4 in an Australian population, +250 g 10 and +286 g 6 in Danish populations), and far exceeds the +81 g attributable only to an increase in parity. These analyses also confirm results from prior studies of the increasing risk of LGA with higher maternal parity and BMI [13,25,26]; the increased risk of SGA with early fetal losses [27]; and the lower birthweight, longer gestation, and lower risk of LGA in female versus male infants [28][29][30].…”
Section: Discussionsupporting
confidence: 85%
“…The longitudinal follow-up revealed that this difference in body size tended to persist throughout infancy, as body weight and height were still significantly smaller than in controls at 3 years of age. It has previously been hypothesized that the gender dimorphism of birth weight and length was caused by fetal androgens (83,84). In our study, boys with severe forms of hypospadias had a birth weight and length similar to or even lower than girls from the same cohort (85), which is similar to another previous report (86).…”
Section: Prevalence Of Cryptorchidism and Hypospadiassupporting
confidence: 90%
“…Zegher et al (1998), menemukan bahwa anak laki-laki lebih berat daripada anak perempuan pada saat kelahiran. Perbedaan berat lahir antara anak laki-laki dan anak perempuan dihasilkan oleh aksi androgen.Androgen merupakan elemen kunci untuk diferensiasi genetalia internal dan eksternal laki-laki, organ seksual lainnya dan komposisi tubuh secara umum yang bekerja melalui satu reseptor tunggal androgen (Hiort, 2013).…”
Section: Pengaruh Status Gizi (Lila Ibu)unclassified